Karakterisasi dan Identifikasi Isolat Bakteri Endofitik Penghambat Jamur Patogen Padi - Yadi Suryadi; Tri P. Priyatno; I Made Samudra; Dwi N. Susilowati; Patricia Patricia; Wahyu Irawati (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2013)
Disease caused byfungal pathogens often causing damage on rice crop. Thisstudy was aimed to characterize 10 endohytic bacterial isolatesin suppression of rice pathogenic fungi. Characterization by invitro test showed several endophytic isolates effective againstfungal pathogen Rhizoctonia solani (Rs) and Pyriculariaoryzae (Po). The bacterial culture filtrates could inhibit radialgrowth of fungal colonies with the Rs ranged percentageinhibition of 32.9-99.4%, whilst inhibition against Po wereranged from 3-98.2%, respectively. Based on chitinase assay,it was indicated that gram negative bacteria of E 76 isolateproduced clear zone and highest chitinolytic index. Theanalysis to the base sequence (total 1,322 bp) using 16s rRNAgene sequencing revealed that E76 isolates had 99% similaritywith Burkholderia sp.